"Double-Pulley" Dual-Row Technique for Arthroscopic Fixation of Large Bony Bankart Lesion: Minimum 2-Year Follow-up With CT Evaluation. Issue 9 (13th September 2021) - Guo, Siyi; Jiang, Chunyan
Background: A "double-pulley" dual-row technique had been applied for arthroscopic fixation of large bony Bankart lesion in which the fragment has a wide base. Purpose: To investigate clinical outcomes and glenoid healing after arthroscopic fixation of bony Bankart lesion using the double-pulley dual-row technique. Study Design: Case series; Level of evidence, 4. Methods: A total of 25 patients were included in this retrospective study. The American Shoulder and Elbow Surgeons (ASES) score, pain visual analog scale (VAS) score, and range of motion of the affected shoulder were assessed. Radiographs and computed tomography (CT) scans (preoperatively, immediately after surgery, and at 1 year postoperatively) were performed to evaluate arthritic changes (Samilson-Prieto classification) and glenoid size. The intraobserver reliability of the CT measurements was analyzed. Results: At a mean follow-up of 3.4 years, the mean ASES and VAS scores were 94.87 ± 5.02 and 0.48 ± 0.59, respectively. Active forward elevation, external rotation with the arm at the side, and internal rotation were 165.80° ± 11.70°, 33.20° ± 8.02°, and T9 (range, T6-S1), respectively. No patient reported a history of redislocation or instability. The intraobserver reliability of the CT measurements was moderate to excellent. The mean preoperative size of the bony fragment was measured as 23.4% ± 7.8% of the glenoid articular surface. The quality of the reduction was judged to be excellent in 13 (52%) cases, good in 8 (32%), and fair in 4 (16%). The mean immediate postoperative glenoid size was 96.8% ± 4.3%, and bone union was found in all cases. There were no significant differences between reconstructed and immediate postoperative glenoid size or between preoperative and final Samilson-Prieto grades. Conclusion: The arthroscopic double-pulley method was a reliable technique for the fixation of large bony Bankart lesions with a wide base. Satisfactory results can be expected regarding the restoration of the glenoid morphology and stability of the shoulder. High healing rate and good shoulder function can be achieved. No radiological evidence of cartilage damage caused by suture abrasion was found at 2- to 5-year follow-up.